EUROPEAN GREEN DEAL: INSTITUSIONALISM UNI EROPA DALAM MENGHADAPI ISU PERUBAHAN IKLIM - Fithriana, Arin; Dewi, Estefania Santika (Universitas Jenderal Ahmad Yani, 2023)
his research analyzes the efforts of the European Union (EU) in overcoming climate change through the European Green Deal (EGD). Neoliberalism perspectives, Neoliberal institutionalism theory, and sustainable development are used to further analyze energy transitions and sustainability in EGD. The importance of EGD to the EU climate policy sustainability shows the expansion of sector coverage and progress in achieving the goal, being climate neutral by 2050. Through EGD, the EU is carrying out an energy transition with a wider sector coverage, such as buildings, industry, food, and agriculture. In order to achieve common goals, it is necessary to implement EGD as the European Union's foreign policy. EU efforts through EGD policies and strategies are renewable energy, REPowerEU, Farm to Fork strategy, deforestation strategy, New European Bauhaus, and the European Sustainable Investment Plan to support the sustainability of EGD on financial allocation with a just transition mechanism